Carboxy-Endcapped Conductive Polypyrrole: Biomimetic Conducting Polymer for Cell Scaffolds and Electrodes - Lee, Joo-Woon (2006)
Numerous regenerating tissues respond favorably to electrical stimulation, creating a need for a bioactive conducting platform for tissue engineering applications. The drive for biosensors and electrode coatings further requires control of the surface properties of promising conductive materials such as polypyrrole. Here we present carboxy-endcapped polypyrrole (PPy-α-COOH), a unique bioactive conducting polymer with a carboxylic acid layer, composed of a polypyrrole (PPy) surface modified with pyrrole-α-carboxylic acid (Py-α-COOH). This unique structure is simple to produce, provides a stable bioactive surface via covalent bonds, and preserves bulk properties such as electrical conductivity and mechanical integrity. The chemical structure of this polymer composite was characterized by angle-resolved X-ray photoelectron spectroscopy (XPS), which demonstrated the presence of carboxylic acid functionality on the top surface of conductive PPy. A four-point probe test was used to verify the similar conductivity of PPy-α-COOH compared to that of standard PPy. To demonstrate the potential to influence cellular activity, the carboxylic acid monolayer surface was grafted with the cell-adhesive Arg-Gly-Asp (RGD) motif. Human umbilical vein endothelial cells (HUVECs) cultured on RGD-modified PPy-α-COOH demonstrated significantly higher adhesion and spreading than on the negative controls PPy-α-COOH and unmodified PPy.